PERILAKU MEKANIK BETON MUTU TINGGI DENGAN MENGGUNAKAN SILICA FUME SEBAGAI BAHAN TAMBAH - Alex Kurniawandy; Zulfikar Djauhari; Muhammad Refi (Jurnal APTEK, 2011)
The purpose of this study was to assess the effect of adding silica fume in high strength concrete mix to the mechanical behavior of concrete through the study of compressive strength, elastic modulus, shrinkage and also an analysis of Scanning Electronic Microscope (SEM). Supeplasticizer mixture composition used in this study is 1% for all the variations and the use of silica fume with a variation of 0%, 5%, 10%, 15%, and 20% by weight of cement. The specimens used were cylindrical with a diameter of 150 mm and height 300 mm, 40 sampel.Mutu concrete planned more than 40 MPa were tested at 28 days with the first treatment before testing. The results showed that the highest compressive strength of concrete contained in a mixture of silica fume concrete with the use of 5% that of 43 MPa. Concrete splitting tensile strength value of the highest obtained in this study is a variation of 5% silica fume which is 3.64 MPa. Elastic modulus on the use of silica fume 5% nerupakan largest value is 3.5944 x 104 MPa.